"I'm in this world for a reason": Resilience and recovery among American Indian and Alaska Native two-spirit women. Issue 3 (1st October 2016) - Elm, Jessica H. L.; Lewis, Jordan P.; Walters, Karina L.; Self, Jen M.
ABSTRACT: American Indian and Alaska Native sexual minority (two-spirit) women are vulnerable to substance misuse and mental health challenges due to multiple minority oppressed status and exposure to stress and trauma. Yet, these women find pathways toward healing and wellness. We conducted a qualitative data analysis of interviews derived from a national health study and gained an understanding of 11 two-spirit women's resilience and recovery patterns. Emergent from the data, a braided resiliency framework was developed which elucidates multilayered abilities, processes, and resources involved in their resiliency. We recommend that resilience-promoting strategies be incorporated into substance misuse and mental health interventions.